If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2x + -2) + 8x + -4 = 0 Reorder the terms: -3(-2 + 2x) + 8x + -4 = 0 (-2 * -3 + 2x * -3) + 8x + -4 = 0 (6 + -6x) + 8x + -4 = 0 Reorder the terms: 6 + -4 + -6x + 8x = 0 Combine like terms: 6 + -4 = 2 2 + -6x + 8x = 0 Combine like terms: -6x + 8x = 2x 2 + 2x = 0 Solving 2 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = 0 + -2 2x = 0 + -2 Combine like terms: 0 + -2 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| 1.2s=1.44 | | 4x^3y^8-7x^5y^6= | | -3(3s-1)-3=-3(8s+3)-5 | | Ax=15+box | | p^2=-5p+66 | | 5y+4=y-2 | | m/3-2=11 | | .06x+.09(x+200)=63 | | 3x+2x=29 | | X/x-22 | | 6y^2-1y-1=0 | | s=40+.5s | | 8x^2+8x=3-2x | | x^2+8x^2=3-2x | | 10z-z=9z | | T=5k+v | | e^7-3x=9 | | 8x-20=8x-20 | | R/4-r/14=1/4 | | x^2+8x=3-2x | | 8t-6=3(t+1)+3 | | A=kp | | 9x=x(2)+8 | | 2x=x(2)-7x+8 | | 2x=x(2)-7x | | x-.15=.42 | | 6(t-3)+4t=5(2t+3)-12 | | 3x^2+6x+9=2x^2 | | 12y-18=4y+6 | | (3x+23)+(x^2+49)=180 | | 4(11x-10)+6=8x-5 | | 3w-16w=52 |